Ecological and life‐history correlates of enamel growth in ruminants (Artiodactyla). (August 2014) - Jordana, Xavier; Marín‐Moratalla, Nekane; Moncunill‐Solé, Blanca; Köhler, Meike
<x xml:space="preserve">Abstract</x> Enamel incremental markings are widely used to reconstruct growth patterns of extinct mammals. However, the likely existence of an allometric relationship between dental morphology and enamel growth suggests that caution is required when making life‐history inferences based on these microstructures. In the present study, we aimed to explore the potential of using enamel growth rate as a reliable proxy of the pace of life in fossil species. We sectioned 24 permanent first lower molars from 19 extant and two fossil ruminant species. By using polarized light microscopy, we measured the two parameters that determine enamel growth rates: daily secretion rate (DSR) and extension rate, as quantified by enamel formation front (EFF) angle. These parameters were regressed against body mass, hypsodonty index, and relative age at first reproduction (relative to body mass) as a proxy for the species' pace of life, using phylogenetic generalized least squares analyses. Our results indicate that DSR conforms to the allometric relationship because it is positively correlated with hypsodonty. By contrast, enamel extension rate is strongly related to the pace of life. These findings suggest that the two mechanisms of enamel growth might be subject to different selective forces. The application in two fossil species provides evidence that EFF angle is a reliable proxy of the life history of extinct mammals. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 657–667.